Perbandingan Vitrektomi dengan dan tanpa Internal Limiting Membrane Peeling pada Membran Epiretina Idiopatik: Meta-Analisis - Dana Paramitha Putri; Qonita Widia Nabilah; Bagus Mahendra Satya Wiraputra; Alfelia Ezrabica Telussa (Jurnal Klinik dan Riset Kesehatan, 2026)
Background: Epiretinal Membranes (ERMs), also widely mentioned as macular puckers, are fibrocellular membranes which avascular and semi-translucent that cover the retinal surface. Complaints caused by ERM include visual impairments such as micropsia, macropsia, metamorphosis, monocular diplopia, and even blindness. Internal limiting membrane (ILM) peeling recently introduced as acceptable option for treating ERM, but the effectiveness of the procedure is still debatable. Aim: To compare the clinical outcomes of vitrectomy procedure with ILM peeling or without it for idiopathic ERM treatment. Methods: Study recorded relevant prospective or retrospective studies published in 2014-2024 by searching PubMed, Cochrane, Scopus, and ScienceDirect database. The mean change in BCVA and CMT was analyzed as a continuous variable, reported using Weighted Mean Difference (WMD) with 95% CI and heterogeneity was assessed using the chi-square test and I2 statistics. Result: There were 4 relevant studies with adequate data published in the last 10 years. 163 eyes consisted of 82 eyes in the No-ILM peeling group and 81 eyes in the ILM peeling group. Postoperative BCVA did not differ significantly between the two groups (MD -0,01; 95% CI: -0,07 to 0,06; P = 0,85) and no significant difference was found between the two groups in postoperative CMT (MD 7.70; 95% CI: -20.11 to 35.52; P = 0.59). Conclusion: There was no significant difference in BCVA and CMT between vitrectomy with and without ILM peeling in patients with idiopathic epiretinal membrane.